Three essays on trade and biodiversity - Alam, Rafat (University of Ottawa (Canada), 2006)
The thesis is motivated on the background of rapid biodiversity depletion around the world. Using a general equilibrium model, the first essay shows how free trade can have negative impacts on the biodiversity stock of the South due to missing markets. It also shows that free trade added with Southern rapid population growth and agricultural extensions are the main reasons of biodiversity loss. Demand side mechanisms like discounting of biodiversity depleting products and supply side mechanism like ecofriendly agricultural technologies can have a positive impact to decrease biodiversity loss. Essay two shows how absence of a market for ecosystem services causes depletion of biodiversity in the developing countries. In any period, the amount of land development in the south depends on how large the relative size of the southern younger generation in that period is, compared to the size of the maximum available land resources. Lack of any other assets in the South for old age savings, low land clearing cost and low discount rate causes biodiversity loss. There is scope of conserving biodiversity and the flow of ecosystem services by fiscal tools like land development fee or land tax and market creation through payment for ecosystem services. But these policies may deteriorate Southern terms of trade. Through a two period general equilibrium model with an open economy, paper three shows how bio-prospecting can help in the conservation of biodiversity and under what conditions it can fail. The paper shows that a systematic search process depending on prior information on the plant species and the health characteristics increases the success of bio-prospecting. Also a lower cost of the bio-prospecting process or manufacturing of drugs, a high probability of drug discovery, and a drug with a high benefit result in a higher royalty payment to the South and conservation of biodiversity. Strategic pricing by the bio-prospecting firms or marketing of only high benefit drugs ensure successful bio-prospecting schemes. A larger set of bio-prospected drugs may drive away the low-benefit drug firms out of market. The caveat is that bio-prospecting process may ignore Southern low-value diseases. The three essays of this thesis suggest that green consumerism, payment for ecosystem services or bio-prospecting scheme can be viable tools for biodiversity conservation. But the strong message in all the three essays is also that there is no one miracle tool that can save biodiversity. So a mix of market and non-market tools has to be used for the conservation of world's biodiversity.
Keywords: Economics, Theory.